Rainfall estimation and ground clutter rejection with dual polarization weather radar - F. Lombardo; F. Napolitano; F. Russo; G. Scialanga; L. Baldini; E. Gorgucci (Advances in Geosciences, 2006)
Conventional radars, used for atmospheric remote sensing, usually operate at a single polarization and frequency to estimate storm parameters such as rainfallrate and water content. Because of the high variability of the drop size distribution conventional radars do not succeed in obtaining detailed information because they just use horizontal reflectivity. The potentiality of the dual-polarized weather radar is investigated, in order to reject the ground-clutter, using differential reflectivity. In this light, a radar meteorology campaign was conducted over the city of Rome (Italy), collecting measurements by the polarimetric Doppler radar Polar 55C and by a raingauge network. The goodness of the results is tested by comparison of radar rainfall estimates with raingauges rainfall measurements.